The association between self-esteem and happiness differs in relationally mobile vs. stable interpersonal contexts - Sato, Kosuke; Yuki, Masaki (Frontiers in Psychology, 2014)
Does a change in the nature of surrounding social context affect the strength of association between self-esteem and happiness? This paper aims to answer this question from a socio-ecological perspective, focusing on the role of relational mobility. Recent research has shown that this association is stronger in societies that are higher in relational mobility, where there is a greater freedom of choice in interpersonal relationships and group memberships. In this study, we tested if this hypothesis could be applied to situational differences within the same physical setting. Using a quasi-experimental design, we tested if the association between self-esteem and happiness was stronger for first-year students at a Japanese university who had just entered the college and thus were in a relatively higher mobility context, than the second year students at the same university whose relationships tended to be more stable and long-standing. The results showed, as predicted, that the association between self-esteem and happiness was stronger for the first-year students than for the second-year students. Implications for the theory and research on social change are discussed.